A New Self‐Report Inventory of Dyslexia for Students: Criterion and Construct Validity. (February 2015) - Tamboer, Peter; Vorst, Harrie C. M.
<x xml:space="preserve">Abstract</x> The validity of a Dutch self‐report inventory of dyslexia was ascertained in two samples of students. Six biographical questions, 20 general language statements and 56 specific language statements were based on dyslexia as a multi‐dimensional deficit. Dyslexia and non‐dyslexia were assessed with two criteria: identification with test results (Sample 1) and classification using biographical information (both samples). Using discriminant analyses, these criteria were predicted with various groups of statements. All together, 11 discriminant functions were used to estimate classification accuracy of the inventory. In Sample 1, 15 statements predicted the test criterion with classification accuracy of 98%, and 18 statements predicted the biographical criterion with classification accuracy of 97%. In Sample 2, 16 statements predicted the biographical criterion with classification accuracy of 94%. Estimations of positive and negative predictive value were 89% and 99%. Items of various discriminant functions were factor analysed to find characteristic difficulties of students with dyslexia, resulting in a five‐factor structure in Sample 1 and a four‐factor structure in Sample 2. Answer bias was investigated with measures of internal consistency reliability. Less than 20 self‐report items are sufficient to accurately classify students with and without dyslexia. This supports the usefulness of self‐assessment of dyslexia as a valid alternative to diagnostic test batteries. Copyright © 2015 John Wiley & Sons, Ltd.